The impact of climate change on the European road network - Fifer Bizjak, Karmen; Dawson, Andrew; Hoff, Inge; Makkonen, Lasse; Ylhäisi, Jussi S.; Carrera, Alessandra (Thomas Telford, 2015)
Anticipated climate changes in Europe over the next 100 years were estimated using two different scenarios of carbon dioxide emissions and two computational approaches. The principal manifestations of climate change within the European region are predicted to be a rise in temperature, an increase in rainfall intensity in most areas and a decrease in freeze–thaw cycling. The impacts of such possible climate changes were then estimated for pavements and the pavement-related infrastructure. It should be noted that the life cycle of pavements is much shorter than the time span over which climate change might have a statistically significant influence on pavement performance. Several analytical and numerical analyses were performed in order to simulate the effect of future climate change, taking into account the fact that the effect of these changes on pavements structures will depend on local conditions. In particular, temperature and rainfall increase will be a challenge for asphalts, as both rutting and stripping of asphalt layers can be expected. In countries where roads are presently frequently frozen in winter, the length of this period of freezing will be reduced. For this reason, many thin and unsealed pavements will need to be upgraded if high bearing capacity is to be maintained. In coastal and low-lying areas raised water tables may occur due to areas where flood waters may collect, or due to raised sea levels. For most applications, appropriate responses to these changes in pavement performance will be achievable through the use of new design criteria with regard to temperature and the return period of storm flows. More attention needs to be paid to drainage systems, which should be self-cleaning and easy to inspect.